Characteristics of Spanish Mackerel (Scomberomorus commerson) Bone Gelatin for Ice Cream Stabilizer - Rahimah, Souvia; Fadhila, Anisa; Lembong, Elazmanawati; Sukri, Nandi; Cahyanto, Tri (Indonesian Journal of Halal Research, 2020)
Ice cream is a milk-processed-based product that provides enough nutrients. The ice cream making process requires a stabilizer. The stabilizer used in this study was gelatin. This research used mackerel fish bones as the basic material for the gelatin, where the protein content is high enough to be made as gelatin. The purpose of this research was to determine the right amount of mackerel to make ice cream with good characteristics. The descriptive experimental method with an advanced regression analysis method was used to analyze the results of ice cream physical characteristics, while randomized block design (RBD) and descriptive method were used on the organoleptic results of the ice cream. The experiment consisted of four repetition sessions with different gelatin concentrations of 0%, 0.1%, 0.3%, and 0.5%, each treatment was repeated three times. The results showed additions of gelatin concentration on ice cream making had a very strong relationship with the characteristics of the ice cream namely overrun value, melting power, and viscosity with a correlation coefficient of 0.94, 0.911, and 0.995 respectively. While in terms of organoleptic, the higher the concentration gelatin, the softness of ice cream is higher, therefore more panelists preferred it.